Adherence to 24-hour movement guidelines, BMI, and academic performance in primary school children - Adhe Saputra; Sukendro Sukendro; Haryanto Haryanto; Muhammad Ali Muhammad Ali; Imam Safei (Universitas Nusantara PGRI Kediri, 2026)
The 24-Hour Movement Guidelines integrate physical activity, screen time, and sleep as interrelated behaviors that influence children’s health and academic outcomes. However, evidence from Indonesian primary school populations remains limited. This study aimed to examine adherence to the 24-Hour Movement Guidelines and to analyze its associations with body mass index (BMI) and academic performance among primary school children in Jambi City. A cross-sectional study was conducted involving 325 students (mean age 9.79 ± 0.90 years). Physical activity was assessed using the PAQ-C, screen time through a sedentary behavior questionnaire, and sleep quality using the Pittsburgh Sleep Quality Index (PSQI). BMI was calculated from measured height and weight, and academic performance was obtained from school records. Data were analyzed using descriptive statistics, Chi-square tests, Pearson correlation, and multiple linear regression. Overall adherence to all guideline components was low. Regression analysis showed that physical activity was negatively associated with BMI (B = –0.027, p = 0.006), while screen time (B = 0.056, p = 0.016) and sleep quality score (B = 0.041, p < 0.001) were positively associated with BMI. In relation to academic performance, sleep quality showed a positive association (B = 0.079, p < 0.001), followed by screen time (B = 0.107, p = 0.039), whereas physical activity showed a negative association (B = –0.066, p = 0.002). The results demonstrate that each component of movement behavior exhibits distinct statistical associations with BMI and academic performance among primary school children, without implying causal relationships due to the cross-sectional design.